Influence of human leucocyte antigen-DRB1 on the susceptibility to rheumatoid arthritis and on the production of anti-cyclic citrullinated peptide antibodies in a Portuguese population. Issue 2 (22nd June 2006) - Ligeiro, D; Fonseca, J E; Abade, O; Abreu, I; Cruz, M; Nero, P; Cavaleiro, J; Teles, J; Trindade, H; Caetano, J M; Branco, J
Abstract : Objective: To clarify the influence of the HLA-DRB1 locus on the susceptibility to rheumatoid arthritis and the production of anti-cyclic citrullinated peptide antibodies (anti-CCP) in a Portuguese population. Methods: 141 patients with rheumatoid arthritis fulfilling the American College of Rheumatology 1987 revised criteria for rheumatoid arthritis were compared with 150 healthy controls. Human leucocyte antigen (HLA)-DRB1 locus genotyping was assessed by polymerase chain reaction reverse probing assays and sequence-specific primers. Anti-CCP antibodies were quantified by ELISA in patients with rheumatoid arthritis. Frequencies between groups were compared by the two-sided Fisher's exact test and considered significant if p<0.05. Results: The HLA-DRB1*04 and HLA-DRB1*10 groups were highly associated with rheumatoid arthritis (p<0.001 and p = 0.031, respectively). High titres of anti-CCP antibodies were largely associated with the presence of HLA-DRB1*04/10. Conclusion: The well-recognised susceptibility alleles to rheumatoid arthritis, HLA-DRB1*04, were associated with rheumatoid arthritis in Portuguese patients. The relatively rare DRB1*10 was also associated with rheumatoid arthritis, as was described previously in other southern European countries. Both groups were associated with high anti-CCP titres, reinforcing its relevance to disease onset.